Diary of a wimpy kid the ugly truth - Kinney, Jeff (Amulet Books, 2010)
While trying to find a new best friend after feuding with Rowley, middle-school slacker Greg Heffley is warned by older family members that adolescence is a time to act more responsibly and to think seriously about his future.